Controlled single bubble cavitation collapse results in jet-induced injury in brain tissue. (October 2017) - Canchi, Saranya; Kelly, Karen; Hong, Yu; King, Michael A.; Subhash, Ghatu; Sarntinoranont, Malisa
Abstract: Multiscale damage due to cavitation is considered as a potential mechanism of traumatic brain injury (TBI) associated with explosion. In this study, we employed a TBI relevant hippocampal ex vivo slice model to induce bubble cavitation. Placement of single reproducible seed bubbles allowed control of size, number, and tissue location to visualize and measure deformation parameters. Maximum strain value was measured at 45 µs after bubble collapse, presented with a distinct contour and coincided temporally and spatially with the liquid jet. Composite injury maps combined this maximum strain value with maximum measured bubble size and location along with histological injury patterns. This facilitated the correlation of bubble location and subsequent jet direction to the corresponding regions of high strain which overlapped with regions of observed injury. A dynamic threshold strain range for tearing of cerebral cortex was estimated to be between 0.5 and 0.6. For a seed bubble placed underneath the hippocampus, cavitation induced damage was observed in hippocampus (local), proximal cerebral cortex (marginal) and the midbrain/forebrain (remote) upon histological evaluation. Within this test model, zone of cavitation injury was greater than the maximum radius of the bubble. Separation of apposed structures, tissue tearing, and disruption of cellular layers defined early injury patterns that were not detected in the blast-exposed half of the brain slice. Ultrastructural pathology of the neurons exposed to cavitation was characterized by disintegration of plasma membrane along with loss of cellular content. The developed test system provided a controlled experimental platform to study cavitation induced high strain deformations on brain tissue slice. The goal of the future studies will be to lower underpressure magnitude and cavitation bubble size for more sensitive evaluation of injury. Graphical abstract: Highlights: Brain tissue response to single bubble cavitation due to blast loading quantified. Maximum strain measured at 45 µs after bubble collapse. Dynamic range of threshold strains for cortical tearing estimated. Composite injury maps demonstrate overlap of injury and maximum strain. Cavitation-exposed neurons characterized by disintegrating plasma membrane.